Knowledge and Practice of Diabetics towards Their Disease at Tertiary Care Hospital - Sarah Hussain Sharif; Kausar Abbas Saldera; Muhammad Tanveer Alam; Zia Ullah Khan; Ahsan Mobin (KARACHI MEDICAL AND DENTAL COLLEGE, 2024)
Objective: To assess the knowledge and practice of diabetics towards their disease at tertiary care Hospital. Methods: This is cross sectional study was conducted at department of Diabetic Clinic, Jinnah Postgraduate Medical Centre and Civil Hospital, Karachi from August 2022 to December, 2023.Total 250 diabetic patients of age 18-80 years, either gender, were included in this study. Disabled, blind and patients not willing to participate, were excluded. All relevant features including age, gender, duration of disease, educational status, family history, basic knowledge about diabetes, symptoms, risk factors, complications, prevention, frequency and monitoring of blood glucose, self-exercise practice, weight monitoring, eye checkup, foot care and dietary practice were recorded on a structured questionnaire. SPSS version 10 was used for data analysis. Results: A total of 250 patients were enrolled in this study 100(40%) were males and 150(60%) were females. Majority were in the age group between 41 and 50 years. 65 (26%) were not aware of the term diabetes. Majority had a fairly good knowledge about symptoms, risk factors, complications and prevention of diabetes however most were unaware of its types, 65% were not practicing exercise, 58% were not getting their eye checkup and majority did not practice foot care. Conclusion: Despite having satisfactory knowledge, the practice of the patients was not up to the mark. A multidisciplinary approach is required to motivate patients to actively participate in self-management of the disease